TPACK-based HOTS in Teaching Writing for Promoting EFL Learning Quality on Higher Education: Applying “Program Merdeka Belajar – Kampus Merdeka and Kurikulum Paradikma Baru” - Bagus Waluyo; Umi Nahdiyah; Cholida Indrian Fahriana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
The purpose of the study is to describe the technology on TPACK-based HOTS applied by lecturers of a suburban university in teaching writing, and its challenge faced in-class interaction. Four English lecturers from Universitas Nahdlatul Ulama Blitar in Indonesia are the participants selected using the purposive sampling design. The process of data collection uses depth interviewing through the online system. Data are analyzed using a